Behavioural responses to predators in Mediterranean mussels (Mytilus galloprovincialis) are unaffected by elevated pCO2. (October 2020) - Clements, Jeff C.; Poirier, Luke A.; Pérez, Fiz F.; Comeau, Luc A.; Babarro, José M.F.
Abstract: Ocean acidification is expected to affect marine organisms in the near future. Furthermore, abrupt short-term fluctuations in seawater p CO2 characteristic of near-shore coastal regions and high-density aquaculture sites currently have the potential to influence organismal and community functioning by altering animal behaviour. While anti-predator responses in fishes exposed to elevated p CO2 are well documented, such responses in benthic marine invertebrates are poorly studied. We used high frequency, non-invasive biosensors to test whether or not short term (3-week) exposure to elevated p CO2 could impact behavioural responses to the threat of predation in adult Mediterranean mussels from Galicia on the northwestern coast of Spain. Predator alarm cues (crushed conspecifics) resulted in a prolonged (1 h) reduction in the degree of valve opening (−20%) but had no clear effect on overall valve movement activity, while elevated p CO2 did not affect either response. Our results add to the increasing body of evidence suggesting that the effects of end-of-century p CO2 levels on marine animal behaviour are likely weak. Nonetheless, longer-term exposures spanning multiple generations are needed to better understand how ocean acidification might impact behavioural responses to predation in marine bivalves. Highlights: Tested effects of elevated CO2 on valve gaping responses to predator alarm cues in Mediterranean mussels. Mussels reduced valve gaping in response to predator alarm cues; no change in valve movement activity. Elevated CO2 had no effect on baseline behaviour nor responses to predator cues. Behavioural responses to predator cues in bivalves appear robust to high CO2 .